The effects of different degrees of leg length discrepancy on vertical ground reaction force in children and adults: treatment implications - F, Mohamed-Saaid; AR, Sulaiman; I, Munajat; EF, Mohd; WN, Arifin; R, Ghafar (Malaysian Orthopaedic Association, 2023)
Introduction: Previous studies on the degree of leg length discrepancy that causes limb biomechanical problems did not differentiate between adults and children. We conducted this study to determine the effects of simulated leg length discrepancy on vertical ground reaction force in children and adults to enable decision-making for intervention in patients with leg length discrepancy for different age groups or heights. Materials and methods: This cross-sectional study involved male volunteers of children 150cm and adults with 170cm in height. Vertical ground reaction force was measured using a gait analysis study. The first measurement was taken without any leg length discrepancy as a baseline. Subsequently, different amounts of leg length discrepancy were simulated on the left leg with shoe lifts of 2, 3, and 4cm. The measurements were repeated on each volunteer with similar shoe lifts on the right leg. Therefore, 14 volunteers provided simulations of 28 leg length discrepancies for each group. The first and second peaks of vertical ground reaction force were separately analysed. The vertical GRF of a simulated leg length discrepancy was compared with the baseline. Repeated measurement of analysis of variance (ANOVA) within each group was done. Results: In both groups, the second peak of vertical ground reaction force in the longer leg reduced gradually as the shoe lift increased sequentially from 2 to 3cm and then to 4cm. A discrepancy of 3cm and above was statistically significant to cause a reduction in the vertical GRF on the longer limb in both height groups. Conclusion: The degree of leg length discrepancy that caused significant changes in second peak ground reaction force in children with 150 and adults with 170cm height population was similar at 3cm. Therefore, the cut-off point for intervention for both groups are similar with additional consideration of future growth in children.